KEBERADAAN EWOM DAN KEPUTUSAN BERKUNJUNG KE TEMPAT WISATA DI INDONESIA - Rachmaniar, Rachmaniar; Renata Anisa (Bajang Institute, 2024)
The aim of this research is to examine the existence of eWOM in relation to decisions to visit tourist attractions in Indonesia. The method used in this research is the literature study method. The objects of this research are five empirical studies that explain the power of eWOM for the tourist attractions Gili Trawangan Lombok, Nusa Penida, Carangsari Tourism Village, Hillpark Sibolangit, and Eptilu agrotourism. Data collection techniques are carried out through editing, organizing and finding. The research results show that 1) the five empirical studies show that eWOM is related to people's decisions to visit certain tourist attractions; 2) empirical studies show that eWOM is the strongest variable compared to brand image and eTRUST in relation to people's decisions to visit certain tourist attractions; 3) in empirical studies, the positive eWOM dimension can be elaborated with eWOM Goyette et al (2010) to measure the existence of eWOM in relation to people's decisions to visit certain tourist attractions; and 4) in empirical studies, we can compare eWOM with the theory of Planned Behavior, Source Credibility, and Elaboration Likelihood Model to measure the existence of eWOM in relation to people's decisions to visit certain tourist attractions